Potencial de desenvolvimento rural sustentável presente no patrimônio imaterial da cultura alimentar - Heinrich, Rafael Cristiano (2019)
This study aims to investigate, analyze and record the traditional gastronomic feasts that occur in the rural area of Marechal Cândido Rondon, Paraná, considered as intangible heritage of the local food culture. The relationship of typical festivals with the concepts of Sustainable Rural Development, Sustainable Development Goals, Food and Nutrition Security were cataloged and analyzed. This case study is of a qualitative and quantitative nature and socio-anthropological methodological conception, aims to know how and why these traditional eating habits are maintained, which there is of most essential and characteristic. Semi-structured interviews, observations, photographs and notes were performed at 20 feasts. In 2018, 16525 meals were marketed at these feasts, which featured a diversity of 59 foods, 61.5% fresh food, 13.4% locally processed food, 19.5% industrially processed food and 5.6%. of ultra-processed food products. In terms of origin, 74% of the food served comes from supermarkets, 13.9% is sourced from partners and / or local family farmers and 12% is donated by members. The most purchased foods from family farms are those used in colonial coffee and the most donated foods are lettuce, chayote, cuca, cassava, eggs, cucumber and cabbage. Traditional gastronomic feasts have the potential to commercialize family farming products, stimulating sustainable rural development, contributing to the achievement of the goals of the 2030 Agenda, sustainable development goals and promoting food and nutritional sovereignty and security, as well as facilitating intergenerational transmission of food culture.